MXene-Based Wearable Contact Lenses: Integrating Smart Technology into Vision Care - Khosravi, Arezoo; Zarepour, Atefeh; Zarrabi, Ali; Iravani, Siavash (Nano-Micro Letters, 2025)
MXene-based smart contact lenses demonstrate a cutting-edge advancement in wearable ophthalmic technology, combining real-time biosensing, therapeutic capabilities, and user comfort in a single platform. These devices take the advantage of the exceptional electrical conductivity, mechanical flexibility, and biocompatibility of two-dimensional MXenes to enable noninvasive, tear-based monitoring of key physiological markers such as intraocular pressure and glucose levels. Recent developments focus on the integration of transparent MXene films into the conventional lens materials, allowing multifunctional performance including photothermal therapy, antimicrobial and anti-inflammation protection, and dehydration resistance. These innovations offer promising strategies for ocular disease management and eye protection. In addition to their multifunctionality, improvements in MXene synthesis and device engineering have enhanced the stability, transparency, and wearability of these lenses. Despite these advances, challenges remain in long-term biostability, scalable production, and integration with wireless communication systems. This review summarizes the current progress, key challenges, and future directions of MXene-based smart contact lenses, highlighting their transformative potential in next-generation digital healthcare and ophthalmic care. Highlights: 1 MXene-based smart contact lenses seamlessly combine real-time biosensing, therapeutic functions, and enhanced user comfort, revolutionizing ocular health monitoring and treatment. 2 The use of transparent MXene films enables features like photothermal therapy, antimicrobial protection, and dehydration resistance, significantly improving eye protection and disease management. 3 While stability, scalability, and wireless integration pose hurdles, ongoing advancements suggest these lenses hold tremendous potential for transforming digital healthcare and ophthalmic care.